Retrospective analysis of the provision of urological care to patients with chronic balanoposthitis against the background of carbohydrate metabolism disorders - R. S. Frantsev; A. P. Frantseva (Исследования и практика в медицине)
The study purpose. To conduct a retrospective analysis of the results of providing urological care to patients with chronic balanoposthitis on the background of carbohydrate metabolism disorders..Patients and methods. A retrospective analysis of the results of treatment of phimosis due to chronic balanoposthitis in 95 patients was carried out. All patients were divided into two groups. The 1st group included men who showed signs of impaired carbohydrate metabolism (n = 41; 43.1 %). The 2nd group consisted of patients who had no metabolic disorders (n = 54; 56.9 %). The average age of 41 men of the first group was 48.2 ± 17.5 years, the second group of 54 men – 44.6 ± 15.3 years (p > 0.05). According to the indications, all patients underwent local therapy with antiseptics and antimicrobial drugs. In the presence of frequent relapses of balanoposthitis, persistent pain syndrome, the presence of phimosis according to the indications, circumcision of the foreskin was performed. In all patients, the time of surgery, the volume of blood loss during circumcision, and the duration of wound healing were evaluated. We considered the clinical case completed after complete regeneration of the wound.Results. Conservative therapy of balanoposthitis in patients without impaired carbohydrate metabolism was effective in 85.1 %, and in men with type 2 diabetes mellitus (DM2) only in 9.7 %. Consequently, hyperglycemia reduces the effectiveness of conservative therapy of this disease by eight times. In patients with DM2, circumcision was performed 4.6 times more often than in the control group. The correlation of signs of hyperglycemia and the need for surgical treatment of balanoposthitis was 0.66. The duration of circumcision in group 1 was longer by 7.3 ± 3.6 min. compared with the second group (p < 0.05). Wound healing in patients with DM2 was observed almost twice as long (p < 0.05). Thus, with DM2, balanoposthitis is more difficult to treat. If balanoposthitis has a recurrent course, then circumcision can be considered as the final treatment option.Conclusion. Balanoposthitis in patients with impaired carbohydrate metabolism often has a chronic form. In patients with DM2, conservative therapy of inflammation of the foreskin of the penis is effective in one out of ten cases. In adult men, balanoposthitis was more common in middle and old age. Among patients of this age, 11 (26.8 %) people had hyperglycemia for the first time. Consequently, men of the above age may be at risk and need more careful examination of the external genitalia and control of the level of glycemia.